Morphometric and DNA sexing accurately in male Javan hawk-eagle (Nisaetus bartelsi) determination at Kamojang Eagle Conservation Center, West Java, Indonesia - SUSANTI WITHANINGSIH; MUHAMMAD FADLI ILHAM; AZIIZ MARDANARIAN ROSDIANTO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Withaningsih S, Ilham MF, Rosdianto AM. 2024. Morphometric and DNA sexing accurately in male Javan hawk-eagle (Nisaetus bartelsi) determination at Kamojang Eagle Conservation Center, West Java, Indonesia. Biodiversitas 25: 1167-1173. The Javan hawk-eagle (Nisaetus bartelsi) is a protected and endemic species of eagle in Indonesia whose existence is symbolized by the Garuda Pancasila. Raptors act at the top of the predatory chain and as indicators of environmental health. IUCN data states that N. bartelsi is red-listed as endangered. It is one of Indonesia's most frequently hunted and traded birds, and this trading practice has changed its natural behavior. Therefore, preservation through conservation –one of which is rehabilitation– programs are needed to maintain their sustainability. The ultimate goal of rehabilitation is to release the Javan hawk-eagle back into its natural habitat. In conservation and breeding programs, accurate determination of the sex of raptors is integral to informing conservation decision-making, population management, and research efforts aimed at protecting these iconic birds of prey and their habitats. Therefore, this study aims to determine the sex of male N. bartelsi through morphometric and DNA sexing techniques. The research subjects were seven N. bartelsi rehabilitated at Kamojang Eagle Conservation Center, Garut, Indonesia. Morphometric sexing measurements obtained the following results: two males were consistent upon comparing DNA sexing and Kamonjang Eagle Conservation Centre records observations. Analyses were obtained using primer 2550F/2718R that recognized CHD1-Z and CHD1-W as cleaved. Furthermore, the amplification was successfully read a sexing of N. bartelsi at Kamonjang Eagle Conservation Centre. The analysis primer sets mainly for raptors can assist conservation programs such as breeding programs and data collection for mapping this raptor. In addition, the PCR method can also assist in the accurate management of in-situ and ex-situ conservation.